Development of Javanese Dialogue Text Learning Media with Web s.id in Junior High School - Nurhayati, Feni; Kurniati, Endang (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
Grade VII MTs N 2 Sragen students have difficulty learning Javanese dialogue texts, so they need s.id web-based learning media that can be used so that students can listen, read, write, and speak Javanese dialogue text material. This research aims to develop a learning medium for Javanese dialogue texts with the s.id web. This research and development is carried out in six stages: analyzing potential problems, collecting information, designing products, validating designs, improving products, and limiting trials. The data obtained in this study were through observation, interviews, questionnaires, and tests. The data analysis technique uses qualitative descriptive analysis techniques. The study results show that students and teachers need media to support learning Javanese dialogue text material. The media content needed includes materials, examples, exercises, evaluations, and online dictionaries. The results of the material validation test averaged 88%, while the media validation test averaged 73%, and both showed valid results. The results of the limited trial also received an average of 94.8 or an N-Gain Score of 0.83 ≥ 0.3 with compelling evidence. Therefore, web-based learning media s.id be able to be used and developed into a supporting medium for dialogue text material for class VII MTs N 2 Sragen.